2023
DOI: 10.1021/acsami.3c03437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MnO2 Morphology on Kinetics and Stability in Zinc-Ion Batteries

Abstract: Research on zinc-ion batteries (ZIBs) with manganese-based cathodes has been severely hindered by their poor cycle stability. This study explores the fundamental parameters that affect the cycle stability of battery systems from a structural stability perspective. MnO2 electrodes with different classical morphologies and sizes were synthesized via a temperature-controlled coprecipitation strategy. The effects of the morphology and size of the MnO2 on the overall electrical properties and kinetics of ZIBs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Aqueous rechargeable batteries are emerging as exciting candidates owing to their improved safety, inexpensiveness, non-pollution characteristics, and good ionic conductivity compared with the organic electrolytes-based counterparts. [5] So far, a variety of aqueous rechargeable batteries have been studied among which zinc-ion batteries (AZIBs) have become much attractive as a result of the high theoretical specific capacity (820 mAh g −1 ) and volumetric capacity (5851 mAh cm −3 ), [6][7][8][9][10] as well as the low redox potential of the Zn anode. [11] In addition, zinc is highly abundant in nature, which could decrease the cost of mass production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous rechargeable batteries are emerging as exciting candidates owing to their improved safety, inexpensiveness, non-pollution characteristics, and good ionic conductivity compared with the organic electrolytes-based counterparts. [5] So far, a variety of aqueous rechargeable batteries have been studied among which zinc-ion batteries (AZIBs) have become much attractive as a result of the high theoretical specific capacity (820 mAh g −1 ) and volumetric capacity (5851 mAh cm −3 ), [6][7][8][9][10] as well as the low redox potential of the Zn anode. [11] In addition, zinc is highly abundant in nature, which could decrease the cost of mass production.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a variety of aqueous rechargeable batteries have been studied among which zinc‐ion batteries (AZIBs) have become much attractive as a result of the high theoretical specific capacity (820 mAh g −1 ) and volumetric capacity (5851 mAh cm −3 ), [ 6 , 7 , 8 , 9 , 10 ] as well as the low redox potential of the Zn anode. [ 11 ] In addition, zinc is highly abundant in nature, which could decrease the cost of mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its easily tuned physical and chemical properties, manganese dioxide (MnO 2 ) has been one of the research focuses in a range of applications, such as electrochemical materials for battery and supercapacitor, and air pollutants degradation catalysts for carbon monoxide (CO), ozone (O 3 ), etc. The basic unit in MnO 2 is six-coordinated [MnO 6 ] octahedra, which constructs different crystallographic phases, such as α-MnO 2 , β-MnO 2 , γ-MnO 2 , δ-MnO 2 , etc., depending on the varied interlinking formats. Different phases are preferred in different applications. For example, Devaraj and Munichandraiah found that the δ-and α-phases have higher specific capacitance than other phases, and similar trends were reported for the CO oxidation by Liang et al However, the γ-MnO 2 has higher O 3 catalytic activity than α-MnO 2 as reported by Li et al Therefore, the structure–property relationships should be further investigated for MnO 2 in varied applications.…”
Section: Introductionmentioning
confidence: 99%